RP-HPLC (STABILITY-INDICATING) BASED ASSAY METHOD FOR THE SIMULTANEOUS ESTIMATION OF DORAVIRINE, TENOFOVIR DISOPROXIL FUMARATE AND LAMIVUDINE - TIRUVEEDHI, V. L. N. BALAJI GUPTA; BATTULA, VENKATESWARA RAO; BONIGE, KISHORE BABU (International Journal of Applied Pharmaceutics, 2021)
Objective: In this study, a RP-HPLC (stability-indicating) based assay method for the estimation of doravirine (DRV), tenofovir disoproxil fumarate (TFF) and lamivudine (LMV) simultaneously in the tablets was described. Methods: The simultaneous analysis of DRV, TFF and LMV was done with HPLC system (Agilent 1100 series) and Luna Phenomenex C18 (250 mm × 4.6 mm × 5 μ) column with isocratic mobile phase (35% volume ratio of methanol and 65% volume ratio of 20 mmol ammonium formate, pH 5). Validation of assay method was done on sensitivity, linearity, accuracy, selectivity, precision, robustness and specificity. Results: The calibration curves were linear through the range of 25-200 µg/ml for DRV and 75-600 µg/ml for TFF and LMV. The percent relative standard deviation for intraday variation/precision, interday variation/precision, intermediate precision/ruggedness and robustness were lower than 2%. The recovery of LMV (99.09-99.76%), TFF (99.10-99.41%) and DRV (98.65-99.28%) confirmed the good accuracy. The stability of LMV, TFF and DRV in 0.1N NaOH, 3% peroxide, 0.1 N HCl, UV light and dry heat of 60 °C was determined. Conclusion: The results have allowed the method to be implemented in the tablets to quantify DRV, TFF, and LMV.